Hermeneutika Jorge J. E. Gracia dan Fazlur Rahman: Kajian Epistemologis-Komparatif dalam Studi Penafsiran Al-Qur’an: Hermeneutics Jorge J. E. Gracia and Fazlur Rahman: An Epistemological-Comparative Study in Qur'anic Interpretation - M Rais Nasruddin (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2026)
This article is based on the fact that the hermeneutic theory developed by Jorge J. E. Gracia has a number of similarities with Fazlur Rahman’s hermeneutic theory, which is widely known in contemporary Islamic studies. It seeks to address three main issues: the epistemological structure of Gracia’s interpretive function and Rahman’s double movement, the factors underlying their similarities and differences, and their contributions to the development of Qur’anic interpretation. Using a qualitative literature approach, this study draws on primary sources from Gracia’s A Theory of Textuality: The Logic and Epistemology and Rahman’s Islam and Modernity: Transformation of an Intellectual Tradition, supported by relevant secondary literature. The analysis employs a descriptive-comparative method, utilizing Abdullah Saeed’s framework of textual and contextual interpretation as an analytical tool. The results of the study show that both figures developed their theories from anxiety about existing interpretive practices, and both emphasized a contextual approach. Gracia focuses on validating meaning through textual implications, while Rahman highlights the moral message of the text. Although they differ in their criteria of validity, both aim to balance objectivity and subjectivity in interpretation. Ultimately, their theories reflect a significant shift in Qur’anic studies from a predominantly textual approach toward a more contextual approach.